Визначення та класифікація об'єктів міжбюджетних правовідносин - Кузьменко, О.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье рассмотрены теоретические аспекты определения объекта межбюджетных отношений и значение этого определения. Определены объект межбюджетных отношений и его виды. In the article the theoretical aspects of determination of object of interbudgetary relations and value of this determination are considered for the legal adjusting of these relations. The object of budget relations and its kinds are determined.